Understanding negotiating journalism: Survival tactics, non-state pressure, and resistance of local media in Madura, Indonesia - Surokim Surokim; Rachmah Ida; Suko Widodo (Center for Sociological Studies and Community Developmen, 2026)
After the Reformation era in Indonesia, discussions of press freedom have mainly focused on institutions, while the everyday experiences of local journalists facing non-state pressures are often overlooked. This study examines interviews with nineteen journalists from four regencies on Madura Island and introduces the concept of negotiating journalism. Local journalists regularly face pressures from blatter, klebun, kiai, contractors, politicians, and predatory NGOs while trying to maintain professional standards. Drawing on the perspectives of Anthony Giddens, Michel de Certeau, and Joel S. Migdal, the study identifies four main findings. First, journalists experience intimidation, verbal abuse, financial loss, and social exclusion. Second, they cope by fact-checking, being polite, building relationships, protecting editors, and finding additional income sources. Third, they resist pressures through negotiation, adherence to norms and rules, investigative reporting, and legal action. Fourth, journalists continuously balance ethical ideals, practical realities, and economic survival. Negotiating journalism is not a form of surrender but a practical strategy for working within a complex environment marked by overlapping authority, weak institutions, and unstable local media economies. The study shows that press freedom is shaped by journalists’ everyday relationships and local-level negotiations.